Analysis of Public Satisfaction Index in Kedungadem Public Health Center: Evaluation of Service Quality in Semester II, 2024 - Rahmawati, Dwi Yana; Siswati, Ayu; Mujanah, Siti; Alifianto, Achmad Yanu (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Objective – This study aims to evaluate the quality of public services and obtaim feedback on the performance of services provided to the community for continuous improvement of service performance based on the Public Satisfaction Index (IKM) at the Kedungadem Health Center in Semester II of 2024. Methodology – This research uses a quantitative descriptive approach through surveys to 100 respondents each from 14 villages and 13 types of health services. The score was measured using data processing techniques for analyzing the IKM. The survey instrument uses a questionnaire that is compiled based on 9 service elements determined by govemment regulations. Findings – The overall IKM value of the Kedungadem Health Center service is 85.40. which is categorized in the